Effect of the Factors of Consumer Behaviour on Purchase of Green Products - Bhatti, Kulbir Kaur; Negi, Abhishek (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936967);" role="presentation">Environmental conditions of the globe are getting adverse. <span dir="ltr" style="left: calc(var(–scale-factor)*316.63px); top: calc(var(–scale-factor)*307.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.954276);" role="presentation">Since industrial revolution the natural cycle of the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909356);" role="presentation">globe <span dir="ltr" style="left: calc(var(–scale-factor)*100.22px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958271);" role="presentation">has been disturbed <span dir="ltr" style="left: calc(var(–scale-factor)*187.48px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.0005);" role="presentation">imparting changes in the <span dir="ltr" style="left: calc(var(–scale-factor)*302.08px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.965842);" role="presentation">biodiversity, <span dir="ltr" style="left: calc(var(–scale-factor)*358.16px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919987);" role="presentation">evolved <span dir="ltr" style="left: calc(var(–scale-factor)*395.80px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.909865);" role="presentation">acid <span dir="ltr" style="left: calc(var(–scale-factor)*418.45px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.89501);" role="presentation">rains, <span dir="ltr" style="left: calc(var(–scale-factor)*446.26px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.863503);" role="presentation">greenhouse <span dir="ltr" style="left: calc(var(–scale-factor)*497.70px); top: calc(var(–scale-factor)*321.17px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.933196);" role="presentation">effect, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*334.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.944747);" role="presentation">contamination of water and soil resources. Traditional marketing had valid drawbacks, it primarily focused on <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934645);" role="presentation">consumers, fulfilled their needs to meet their sa<span dir="ltr" style="left: calc(var(–scale-factor)*267.41px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.950084);" role="presentation">tisfaction level and attain maximum p<span dir="ltr" style="left: calc(var(–scale-factor)*422.86px); top: calc(var(–scale-factor)*347.69px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.981609);" role="presentation">rofits. All this led to use <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.936779);" role="presentation">natural resources abundantly. <span dir="ltr" style="left: calc(var(–scale-factor)*199.61px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.01321);" role="presentation">As an initiative for improving this situation green marketing is adapted by <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927538);" role="presentation">business entities and their customers. Indian market is characterized by mass consume<span dir="ltr" style="left: calc(var(–scale-factor)*429.94px); top: calc(var(–scale-factor)*374.09px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.958695);" role="presentation">rism. Gradually due to <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.874106);" role="presentation">increased awareness, <span dir="ltr" style="left: calc(var(–scale-factor)*160.46px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.930461);" role="presentation">attitude of consumers <span dir="ltr" style="left: calc(var(–scale-factor)*252.05px); top: calc(var(–scale-factor)*387.29px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.937633);" role="presentation">towards green products have substantially elevated. Motive of the <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*400.49px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925728);" role="presentation">study is to identify the effect of consumer behaviour factors towards purchase of green products. These factors <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87336);" role="presentation">were regress<span dir="ltr" style="left: calc(var(–scale-factor)*122.30px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.848578);" role="presentation">ed <span dir="ltr" style="left: calc(var(–scale-factor)*134.54px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918443);" role="presentation">simultaneously <span dir="ltr" style="left: calc(var(–scale-factor)*197.69px); top: calc(var(–scale-factor)*413.81px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.905994);" role="presentation">beta values have been identified to understand their impact on the purchase. This <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93343);" role="presentation">research would give an insight to retailers to <span dir="ltr" style="left: calc(var(–scale-factor)*256.85px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.87692);" role="presentation">understand <span dir="ltr" style="left: calc(var(–scale-factor)*303.79px); top: calc(var(–scale-factor)*427.01px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.911319);" role="presentation">perceptions and views of consumers purchasing green <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*440.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.05318);" role="presentation">products which will help them to sell green pr<span dir="ltr" style="left: calc(var(–scale-factor)*281.09px); top: calc(var(–scale-factor)*440.21px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.998218);" role="presentation">oducts. This will create satisfaction of consumers, save <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*453.43px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.902243);" role="presentation">environment and give competitive advantage to producers and sellers